2017
DOI: 10.1111/jpm.12395
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy in korean older adults: A cross‐sectional survey

Abstract: Introduction Korea is experiencing rapid population ageing, spurring an increased need for mental health services for the elderly. Approximately one-third of Korean older adults experience depressive symptoms, and Korea has the highest elder suicide rate among 34 developed nations. Mental health literacy is an important component of promoting mental health, yet studies on the concept have been conducted in few countries. Aim This study examines the level of mental health literacy among Korean older adults and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 48 publications
(98 reference statements)
4
28
1
Order By: Relevance
“…Social support was the second strongest predictor of MHL. This is consistent with other literature showing that social support positively impacted mental health, 49 was significantly related to MHL among older Korean adults, 50 and was an important factor besides biological and psychological aspects. 51 This study also showed that those who participate in a social group generally have higher MHL.…”
Section: Multiple Regression Analysissupporting
confidence: 92%
“…Social support was the second strongest predictor of MHL. This is consistent with other literature showing that social support positively impacted mental health, 49 was significantly related to MHL among older Korean adults, 50 and was an important factor besides biological and psychological aspects. 51 This study also showed that those who participate in a social group generally have higher MHL.…”
Section: Multiple Regression Analysissupporting
confidence: 92%
“…As the most populous developing country, China has the largest elderly population in the world. Due to the increase of chronic diseases, decrease in physical function, cognitive impairment, loneliness, and widowhood, old people are more likely to have mental health problems [4][5][6][7][8]. Approximately 15% of adults aged 60 and over suffer from a mental disorder, the most common of which are depression and anxiety, and around a quarter of deaths from self-harm are among people aged 60 or above [9].…”
Section: Introductionmentioning
confidence: 99%
“…This study highlights a need for efforts to increase mental health literacy among Cypriot older adults. Research has indicated that older adults exhibit poorer mental health literacy than younger adults, including less accuracy at identifying symptoms of mental disorders, and endorsing fewer sources of treatment for a mental disorder [22,24,25]. It has been proposed that older adults in closer proximity to someone with a mental disorder are more likely to have better mental health literacy, a finding that has the potential to inform mental health education and promotion strategies in this population [22].…”
Section: Discussionmentioning
confidence: 99%
“…Programs that use older adult peer educators/supporters, such as the "older people's champions" of the Healthy Passport programme in England, might make the programs more effective. Mental health campaigns, such as Australia's beyondblue, might increase mental health literacy of older adults [18,25]. In Cyprus, where stigma around mental illness holds a long tradition and persists among the elderly, it is important to use strategies that have the potential to empower this population to proactively attend to their mental health including community-based education and national mental health campaigns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation